Design and Construction of a Battery Powered Cell Phone Charger and Dynamo Movement (Elkom: Jurnal Elektronika dan Komputer, 2025)
Limited access to electricity sources in remote areas or emergency situations often hampers the availability of power for telecommunications equipment. This research aims to design a hybrid charger that integrates battery chemical energy storage and dynamo mechanical energy conversion as an alternative solution. The research method uses Research and Development (R&D) with a quantitative descriptive approach to test voltage stability and charging effectiveness. The prototype is designed to use an 18650 battery, a 12V dynamo, and a voltage regulator module to stabilize the output. The test results show that the integrated regulator succeeded in stabilizing the dynamo voltage fluctuations (range 5–12V) to a constant voltage of 5V which is safe for cellphones. Effectiveness testing for 15 minutes showed an increase in cellphone battery capacity of 5–10% in battery mode and 2–4% in dynamo mode. It was concluded that although the dynamo mode has lower efficiency due to manual rotation variability, this tool is worthy of being implemented as an emergency power supply solution (emergency kit) that is portable, economical, and has reliable energy redundancy.